Customers trust mediation: effect of CSR and service quality towards e-WOM - Rastini, Ni Made; Nurcaya, Nyoman (International research journal of management, IT and social sciences, 2019)
This study aims to explain the effect of Corporate Social Responsibility activities, service quality on customer trust in PT. Bali Regional Development Bank and explained that customer trust encourages customers to do e-word of mouth to others. To achieve this goal, 100 people are used by Bank X customers spread across Bali Province and will be taken by purposive sampling with questionnaires as the method of data collection. Data is processed using Structural Equation Modeling analysis tools. The results of this study indicate that trust mediates the effect of service quality and corporate social responsibility to e-WOM at PT Bank X. The results of this study are expected to be able to contribute ideas to the banking industry, especially PT. Bank X in building long-term trust. The long-term trust of customers will make PT. Bank X can still compete and even be superior to other banks operating in Bali Province. The advantages of PT. BPB Bali will affect the pace of development in Bali Province through the assistance of MSMEs as one of the CSR programs that it does.